Peningkatan Kualitas Tahsin Al-Qur’an Santri melalui Pembelajaran Kitab Matan Tuhfatul Athfal Berbasis Asset-Based Community Development di DKM Al-Islah - Muhammad Toha; Yulia Suryani; Eneng Hamidah; Tia Sri Winangsih; Ranti Ranti (Lembaga Pengembangan Kinerja Dosen, 2026)
Tajwid learning in rural mosque communities (DKM) is generally conventional, unstructured, and has not optimally utilized community potential, resulting in low quality of Qur’anic recitation (tahsin). This community service aims to improve the quality of santri’s Qur’anic recitation at DKM Al-Islah, Pangadegan Village, Pagelaran District, Cianjur Regency, through learning the Matan Tuhfatul Athfal using an Asset-Based Community Development (ABCD) approach. The method applied the ABCD framework through the stages of discovery, design, delivery/action, and reflection and sustainability, involving local ustadz, DKM administrators, and santri as key participants. The results indicate that mapping and utilizing local assets successfully established a more structured, participatory, and sustainable tajwid learning system. The integration of Matan Tuhfatul Athfal with peer learning increased active participation, self-confidence, and accuracy of Qur’anic recitation among santri. Furthermore, the program strengthened the institutional capacity of the DKM and fostered a strong sense of community ownership of the learning process. This study concludes that integrating classical matan-based learning with a community empowerment approach is an effective strategy for sustainably improving the quality of Qur’anic recitation in rural DKM settings.